Medicinal plants in the face of infectious diseases: Perception of their use by university students in the health field (Revista Contexto & Saúde, 2025)
Plants have been used for years as a way to restore and strengthen health. Although the use of medicinal plants is common, health professionals have limited knowledge on this topic, which may compromise the reception of patients who opt for this therapy. This study adopted a cross-sectional observational design with the aim of analyzing the perception of health academics regarding the use of medicinal plants in the face of infectious diseases. An epidemiological questionnaire was completed and sent to the institutional email of the academics via a Google form, containing variables related to medicinal plants and infectious diseases by university students in the health field (pharmacy, nursing, aesthetics and cosmetics, nutrition, dentistry, medicine, veterinary medicine, physiotherapy and psychology) from a Private University located in the northwest region of the state of Paraná, Brazil. Once completed, the results were described and submitted to statistical analysis using the Chi-Square Test (ҳ²) with Fisher's Exact Test. The results showed that the majority of participating students were between 18 and 25 years old (77.35%), mainly female (71.07%), regardless of the area evaluated. The students demonstrated that they knew and used medicinal plants, such as chamomile, lemon balm, mint, ginger, guaco, garlic, and saffron. However, this knowledge is not linked to that acquired during graduation, being equal to popular knowledge. Therefore, it is suggested that this theme be included in the pedagogical curriculum of courses in, at least, elective subjects, in line with the guidelines of the National Policy on Integrative and Complementary Practices and the National Policy on Medicinal Plants and Phytotherapeutics, which, despite being in force since 2006, still face difficulties in curricular insertion due to bureaucratic obstacles.
Keywords: Public Health; Traditional Medicine; Communicable Diseases; Public Policies; Adjuvant Treatment